Partial trisomy 21 with or without highly restricted Down syndrome critical region (HR-DSCR): report of two new cases and reanalysis of the genotype–phenotype association - Maria Chiara Pelleri; Chiara Locatelli; Teresa Mattina; Maria Clara Bonaglia; Francesca Piazza; Pamela Magini; Francesca Antonaros; Giuseppe Ramacieri; Beatrice Vione; Lorenza Vitale; Marco Seri; Pierluigi Strippoli; et al. (BMC Medical Genomics, 2022)
Abstract Background Down syndrome (DS) is caused by the presence of an extra copy of full or partial human chromosome 21 (Hsa21). Partial (segmental) trisomy 21 (PT21) is the duplication of only a delimited region of Hsa21 and can be associated or not to DS: the study of PT21 cases is an invaluable model for addressing genotype–phenotype correlation in DS. Previous works reported systematic reanalyses of 132 subjects with PT21 and allowed the identification of a 34-kb highly restricted DS critical region (HR-DSCR) as the minimal region whose duplication is shared by all PT21 subjects diagnosed with DS. Methods We report clinical data and cytogenetic analysis of two children with PT21, one with DS and the other without DS. Moreover, we performed a systematic bibliographic search for any new PT21 report. Results Clinical and cytogenetic analyses of the two PT21 children have been reported: in Case 1 the duplication involves the whole long arm of Hsa21, except for the last 2.7 Mb, which are deleted as a consequence of an isodicentric 21: the HR-DSCR is within the duplicated regions and the child is diagnosed with DS. In Case 2 the duplication involves 7.1 Mb of distal 21q22, with a deletion of 2.1 Mb of proximal 20p, as a consequence of an unbalanced translocation: the HR-DSCR is not duplicated and the child presents with psychomotor development delay but no clinical signs of DS. Furthermore, two PT21 reports recently published (named Case 3 and 4) have been discussed: Case 3 has DS diagnosis, nearly full trisomy for Hsa21 and a monosomy for the 21q22.3 region. Case 4 is a baby without DS and a 0.56-Mb duplication of 21q22.3. Genotype–phenotype correlation confirmed the presence of three copies of the HR-DSCR in all DS subjects and two copies in all non-DS individuals. Conclusions The results presented here are fully consistent with the hypothesis that the HR-DSCR is critically associated with DS diagnosis. No exception to this pathogenetic model was found. Further studies are needed to detect genetic determinants likely located in the HR-DSCR and possibly responsible for core DS features, in particular intellectual disability.